Enhanced photon emission from free electron excitation of a nanowell - Nussupbekov, Ayan (2022)
Efficient nanoscale light sources are sought after for applications such as sensing, imaging, and the development of photonic circuits. In particular, free electron light sources have gained much attention due to their ability to tune and direct light emission. Here, we show that radiation from free electrons passing through a 100 nm wide nanohole can reach as high as 90% of the theoretical limit. This is accomplished through the introduction of a circular nanoridge around the hole to form a structure we call the nanowell. The power radiated from the nanowell exceeds that of a regular nanohole by over 100 times and that of nanoholes surrounded by other features, such as bullseyes, by similar enhancement factors. Upon varying the structural parameters of the nanowell, the peak output wavelength can be tuned over a broad frequency range from the visible to the near-infrared. This reveals a route to extracting power from free electrons via material nanopatterning.